USING A GERMICIDAL INSTALLATION TO IMPROVE THE ENVIRONMENTAL SITUATION AT A POULTRY FARM - T. L. Mayorova; D. G. Musiyev; R. M. Abduragimova; S. A. Gunashev; G. Kh. Azaev; G. A. Dzhabarova (Юг России: экология, развитие, 2016)
Aim. The aim is to study the effect of bactericidal installation in combination with a device for creating a water curtain on the microclimate in the poultry house and environment. Methods. Epizootic research was carried out according to "epizootic methodology", FGI «Federal Centre for Animal Health» (FGI «ARRIAH»). Gas composition of air was investigated by means of universal gas-analyzer (UG-2); the content of carbon dioxide was measured by Subbotin-Nagorskiy titrimetric method; the amount of dust in the air was measured by a gravimetric (weight) method. Air humidity was calculated by means of August statistical psychrometer. Evaluation of the microbial contamination of air was carried out using the Krotov’s device. Results. The performed studies before and after the air bactericidal purification in a poultry farm showed a reduction of carbon dioxide and ammonia by 2-2.5 times, the total microbial contamination of air by 1.9 times and the dust by 4.3 times. We found a direct link between the increases in the amount of microbial bodies of air depending on the age of the bird. Thus, after air-cleaning in the poultry house room where they kept 15-d-old chicks, we calculated 5 thousand microbial cells per one m3 found (E.coli), and at the age of 45 days, the level of contamination reached 11 thousand microbial bodies. Conclusion. Research in the poultry house reveals that using bactericidal installation paired with water curtain device can significantly reduce the concentration of gases, dust and microorganisms in the air of the house and decrease the release into the environment, which will undoubtedly have an impact on the ecological situation of the environment, animal and human health.